Quantifying controlled productive knowledge of collocations across proficiency and word frequency levels - Nizonkiza, Déogratias (Studies in Second Language Learning and Teaching, 2012)
The present study explores the relationship between controlled productive knowledge of collocations and L2 proficiency, the role of frequency in controlled productive knowledge of collocations, and the quantifiability of controlled productive collocational knowledge growth alongside L2 proficiency and word frequency levels. A proficiency measure and a productive collocation test modelled on Laufer and Nation (1999) were presented to Belgian and Burundian English majors. The results show that scores on both tests distinguish between proficiency levels and, furthermore, highly correlate. This suggests that controlled productive knowledge of collocations develops as proficiency increases, supporting earlier studies (Boers, Eyckmans, Kappel, Stengers, & Demecheleer, 2006; Bonk, 2001; Eyckmans, Boers, & Demecheleer, 2004; Gitsaki, 1999) that had established a relationship between collocational knowledge and L2 proficiency. The results also show that the more frequent the collocations, the better they are known, which highlights the crucial role played by frequency in knowing words (Nation & Beglar, 2007). Furthermore, the number of collocations added can be quantified and we observe moderat egains at beginner and advanced levels, and impressive gains at intermediate levels. This supports and extends Laufer’s (1998) and Zhong and Hirsh’s (2009) findings and lays basic ground work for teaching collocations, the amount of which should increase with proficiency levels.